PENGEMBANGAN MEDIA AJAR DIGITAL BERBASIS KEMAHIRAN ABAD-21 PADA KETERAMPILAN BERBICARA BAHASA ARAB DI UNIVERSITAS PANGERAN DIPONEGORO NGANJUK - Husna, Asmaul; Rowin, Inchinia Angger (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2025)
The objectives of this research are: 1). To describe and analyze the development process of 21st-century skill-based digital instructional media for Arabic Speaking Skills courses at Universitas Pangeran Diponegoro Nganjuk. 2). To describe and analyze the feasibility and effectiveness of using 21st-century skill-based digital instructional media for Arabic Speaking Skills courses at Universitas Pangeran Diponegoro Nganjuk. This research adopts a Research and Development (R&D) methodology, incorporating the ADDIE framework. Data collection methods comprise surveys, in-depth interviews, observational studies, and documentary analysis. Data analysis involves qualitative descriptive techniques and statistical analysis using the t-test formula. The research yields the following results: 1). Instructional Media Development: The ADDIE approach was employed, encompassing analysis, design, development, implementation, and evaluation. 2). Expert Validation: Subject Matter Expert: 90% (highly suitable), Media Expert: 88% (suitable), Language Expert: 92% (highly suitable). Lecturer and Student Feedback: 85% of lecturers found the media helpful for structured learning, and 90% of students felt motivated by engaging and relevant content. Media Effectiveness: Significant improvement in Arabic speaking skills: 20-point (30.7%) increase from pre-test (65) to post-test (85), Statistical analysis (t-test): significant difference between pre-test and post-test scores (p < 0.05). Observations: 80% student participation in speaking activities, and 90% students reported improved speaking fluency and structure. Keywords: Learning Media, Digital Learning, Speaking Skills.